Physiological parameters, weed dynamics and herbicide efficiencies in maize (Zea mays L.) as influenced by sequential application of post-emergence herbicides in Kandahar Afghanistan - Burahanuddin Wiqar; S.L. Jat; C.M. Parihar; Arvind Kumar; K.M. Ahmadzai; Abdul Qadir Nabizada (Annals of Agricultural Research, 2022)
A field experiment was conducted at research farm of Afghanistan National Agricultural Science and Technology University (ANASTU), Kandahar, Afghanistan in a randomized complete block design (RCBD) during summer season of 2017 to evaluate the effect of post-emergence herbicides in maize. The experiment consisted ten treatments and replicated thrice. Among the weed control treatments, at 60-90 DAS sequential application of atrazine @ 1.5 kg/ha pre emergence fb tembotrione 120 g/ha PoE at 25 DAS recorded significantly higher CGR and NAR while, maximum RGR was recorded in T6 (halosulfuron (67 g/ha) as PoE at 25 DAS) at 60-90 DAS and lower value were recorded in weedy check. Sequential application of Atrazine @ 1.5 kg/ha pre-emergence fb tembotrione 120 g/ha PoE at 25 DAS (T10) significantly recorded lower number of weed count (4.82, 9.80 and 22.14 per m2 at 20, 50 DAS and harvest stage, respectively) compared to rest of the treatments, while weedy check recorded significantly higher number of weeds. Among the different weed control treatments at 50 DAS, sequential application of Atrazine @ 1.5 kg/ha pre emergence fb tembotrione 120 g/ha PoE at 25 DAS (T10) recorded significantly higher weed control efficiency (88.8%) and weed control index (78.25%) over all other treatments. Whereas significantly higher weed control index (80.07%) and weed control efficiency (81%) were recorded in halosulfuron 67 g/ha at 25 DAS.